Intelligent Web Based Expert System For Respiratory Disease - Munirah, Mohd. Yusof (2002)

(untitled)
This study involves the development of a prototype web based expert system for respiratory diseases: WebResEX. The system was developed in web-based environment that can be accessed globally through the World Wide Web (WWW). The main purpose of this system is to provide early diagnosis of respiratory disease such as asthma, pneumonia, tuberculosis, chronic bronchitis, occupational lung diseases, lung cancer and heart attack. The medical knowledge is store in the knowledge base in the form of production rules (IFITHEN), while the facts of the problem are store in the working memory. The reasoning processes are located in the inference engine. The backbone of the system was implemented using two web based programming language; Cold Fusion 4.5 and JavaScript. The interface has been developed using Swish 2.0 and Adobe Photoshop while the database has been developed using Microsoft Access 2000.